THE IMPACT OF INFORMAL INTERACTIONS ON ORGANIZATIONAL EFFECTIVENESS IN THE MULTI-AGENT MODEL - Pismiennaya, Anna (Revista Inclusiones, 2020)
The purpose of this study is to analyze the impact of informal interactions in an organization on its effectiveness. The authors consider the organization model that combines a hierarchical management structure and project teams. Informal interactions in the model under consideration represent an inverse relationship between the performance level and higher levels of the management line. The paper presents an analysis of the organization’s behavior using a multiagent model with various adaptation abilities of individual agents. The stationary value for the proportion of agents adapted to changing external conditions was used as a characteristic of organizational effectiveness. The analysis showed the inverse relationship of informal interactions to the organizational effectiveness as a whole and found that the impact of informal interactions became significant at low and medium values of the adaptation abilities of individual agents. Following the analysis results, the authors suggested strategies for improving organizational effectiveness without changing the organization structure, in particular, through the development of informal interactions.